COMPARISON OF VARIOUS EEG ELECTRODE PLACEMENT SYSTEMS TO DETECT EPILEPTIFORM ABNORMALITIES IN INFANTS - Sajeesh Parameswaran (University of Brawijaya, 2021)
Background: Technical difficulties in placement of whole 10-20 electrode system is not uncommon in neonates and infants. Apart from the full channel many centers uses the modified and amplitude integrated EEG montages to identify seizures.